2013
DOI: 10.5430/jnep.v3n9p1
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between care burden and social support in Turkish Alzheimer patients family caregivers: Cross-sectional study

Abstract: Objectives: Most of the Alzheimer's patients are looked after at home by family members. Caregivers who are not prepared for looking after these patients are under pressure because of their increasing needs. Both patients and family members need social support provided by not only healthcare professionals but also family, friends and neighbors in order to cope with their physical, psychological, social and economical problems. This study was conducted in order to determine the relationship between care burden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
25
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 56 publications
(65 reference statements)
7
25
1
2
Order By: Relevance
“…It was also found that the social support decreases as the age of mothers of children with disabilities, relatives of patients with stroke, relatives of patients with Alzheimer's disease and relatives of patients with Parkinson's disease increases (Aras and Tel, 2009;Coşkun and Akkaş, 2009;McRae et al, 2009;Tuna and Olgun, 2010;Yurtsever et al, 2013). The findings in this study are in line with these findings.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…It was also found that the social support decreases as the age of mothers of children with disabilities, relatives of patients with stroke, relatives of patients with Alzheimer's disease and relatives of patients with Parkinson's disease increases (Aras and Tel, 2009;Coşkun and Akkaş, 2009;McRae et al, 2009;Tuna and Olgun, 2010;Yurtsever et al, 2013). The findings in this study are in line with these findings.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, no statistically significant difference was reported between age and the perceived social support in caregivers of patients diagnosed with psychiatric disorders and patients with chronic obstructive pulmonary disease (Aras and Tel, 2009;Tel et al, 2010). On the other hand, social support was found to be higher in male caregivers of patients with Alzheimer's disease (Yurtsever et al, 2013). Since our study was carried out with caregivers of bedridden patients, this may lead to non-discrimination of gender in giving support to the caregivers.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations